1990
DOI: 10.1128/aem.56.10.3081-3087.1990
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physicochemical Factors on the Adhesion to Cellulose Avicel of the Ruminal Bacteria Ruminococcus flavefaciens and Fibrobacter succinogenes subsp. succinogenes

Abstract: Ruminococcus flavefaciens adhered instantly to cellulose, while Fibrobacter succinogenes had the highest percentage of adherent cells after about 25 min of contact between bacteria and cellulose. Adhesion of R. flavefaciens was unaffected by high concentrations of sugars (5%), temperature, pH, oxygen, metabolic inhibitors, and lack of Na+. In contrast, the attachment was affected by the removal of divalent cations (Mg2+ and Ca2+), the presence of cellulose derivatives (methylcellulose and hydroxyethylcellulose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1
4

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(55 citation statements)
references
References 33 publications
(36 reference statements)
2
48
1
4
Order By: Relevance
“…In both strains adhesion was enhanced by the presence of calcium. This is a general phenomenon in cellulolytic bacteria [3,7,8]. Adhesion of these anaerobic bacteria was not influenced by oxydation (experiments with DTT); conversely, adhesion of the two strains is regulated differently by the end-products of cellulolyse: cellobiose and glucose influenccct C401 adhesion whereas adhesion of strain A22 was not sensible to these compounds.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In both strains adhesion was enhanced by the presence of calcium. This is a general phenomenon in cellulolytic bacteria [3,7,8]. Adhesion of these anaerobic bacteria was not influenced by oxydation (experiments with DTT); conversely, adhesion of the two strains is regulated differently by the end-products of cellulolyse: cellobiose and glucose influenccct C401 adhesion whereas adhesion of strain A22 was not sensible to these compounds.…”
Section: Discussionmentioning
confidence: 91%
“…Since 80-88% of the cells could be released from cellulose by two washes (see MA'I'I-:RIALS ANt) M~-:rltotgS) and could adhere again, adhesion of Table 2 Inhibition of strain C401 adhesion by strain A22 " Cells density (strain C401) (mgdw) ml 1) ('ells adhered (strain C401) 10 3 mg dw) cm 2 all isolates to cellulose was, at least in part, reversible. Adhesion of strain A22 to Whatman filter paper has been demonstrated as a largely specific process [4] of many cellulolytic bacteria [3,4,7,8]. Adhcsion analysis of the other isolates revealed the same specificity of attachment to the cellulose.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The pH level of the rumen is important because fibrolytic bacteria are very sensitive towards pH changes [24]. Tolerable level of pH for fibrolytic bacterial is between 6.0 and 7.0 [25]. Van Soest [26] has reported optimal ruminal pH ranges to be 6.10-6.80 for rumen microbial proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…One main function of SC seems to be the removal of oxygen, thus protecting the strictly anaerobic bacteria, namely the cellulolytic microflora (Newbold et al, 1996;Marden et al, 2008;Chaucheyras-Durand and Durand, 2010). Oxygen (O 2 ) is lethal to anaerobic bacteria, and it has been shown that oxygen inhibits the growth and the adhesion of rumen cellulolytic bacteria to cellulose (Roger et al, 1990).…”
Section: Discussionmentioning
confidence: 99%